Nursing Summary: designing a nursing section in the Electronic Health Record: Nursing Summary in EHR - Dionisi, Sara; Di Simone, Emanuele; Alicastro, Gregorio Marco; Angelini, Sara; Giannetta, Noemi; Iacorossi, Laura; Di Muzio, Marco (Acta Biomedica Atenei Parmensis, 2019)
The introduction of new information technologies in healthcare led to major changes in the field of tools for managing and evaluating the assistance. In Italy, an example of applying new technologies to the healthcare context is the realization of Fascicolo Sanitario Elettronico (FSE). The FSE is a tool that collects online data and health and socio-health information that make up the patient’s clinical history. The aim of this review is to analyze which components are needed to organize and structure the information and data within the “Nursing Summary”. Literature searches were conducted using the following available online Databases: CINAHL, PubMed and Cochrane Library. The searches were conducted by analyzing publications from the last five years (2012-2016). The process of selection of articles led to the choice of 14 research studies. Additionally, national guidelines were analyzed, concerning official documents and technical specifications for the development of projects of FSE. The analysis of the scientific literature showed that nursing data in the EHR can be used to develop some Clinical Decision Support Systems. Relevant were also used to clarify how the nursing data could be structured in the “Nursing Summary”. The research findings have identified which could be the main components of a possible nursing section to integrate the FSE. This project is proposed as a preliminary study that needs further development.